Online experience sharing without explicit social interaction does not foster social bonding - Wouter Wolf; Kayley Dotson (Cyberpsychology: Journal of Psychosocial Research on Cyberpspace)
Humans have a unique capacity to bond with others through shared experiences, even in the absence of explicit communication. Yet it is unknown whether this capacity is flexible enough to accommodate the different kinds of virtual environments on which we increasingly rely. In the current pre-registered study, we examined whether this capacity still operates effectively on shared screens during non-communicative video mediated interactions, in dyads and in groups. Participants (N = 144 US participants, 71 female, 72 male, 1 non-binary) either watched a video on a shared screen together with (pre-recorded) partners or watched individually while these partners attended to something else. Equivalence tests showed that self-reported social bonding scores were practically equivalent between conditions. Thus, in contrast to several in-person studies, there was no difference in social bonding between conditions. These results show that, in the absence of explicit communication, some of humans’ most fundamental social bonding mechanisms might not operate as effectively in video mediated social interactions. As such, without sufficient active social or emotional engagement, the social costs of increasingly relying on video mediated social interactions might be greater than previously thought.